Comparative Genomics of Pseudomonas sp. Strain SI-3 Associated With Macroalga Ulva prolifera, the Causative Species for Green Tide in the Yellow Sea - Fu, Huihui; Jiang, Peng; Zhao, Jin; Wu, Chunhui (Frontiers in Microbiology, 2018)
Algae-bacteria associations occurred widely in marine habitats, but contributions of bacteria to macroalgal blooming were almost unknown. In this study, a potential endophytic strain SI-3 was isolated from Ulva prolifera, the causative species for the world’s largest green tide in the Yellow Sea, following a strict bleaching treatment to eliminate epiphytes. The genomic sequence of SI-3 was determined in size of 4.8 Mb and SI-3 was found to be mostly closed to Pseudomonas stutzeri. To evaluate the characteristics of SI-3 as a potential endophyte, the genomes of SI-3 and other 20 P. stutzeri strains were compared. We found that SI-3 had more strain-specific genes than most of the 20 P. stutzeri strains. Clusters of Orthologous Groups (COGs) analysis revealed that SI-3 had the highest proportion of genes assigned to transcriptional regulation and signal transduction compared with the 20 P. stutzeri strains including four rhizosphere bacteria, indicating a complicated interaction network between SI-3 and its host. P. stutzeri is renowned for its metabolic versatility in aromatic compounds degradation. However, a significant gene loss was observed in several aromatic compounds degradation pathways in SI-3, which may be an evolutional adaptation when associate with its host. Dissimilatory nitrate reduction to ammonium (DNRA) and denitrification, two competing dissimilatory nitrate reduction pathways, co-occurred in the genome of SI-3, like most of the other 20 P. stutzeri strains, based on the KEGG analysis. We speculated DNRA of SI-3 may contribute competitive advantage in nitrogen acquisition of U. prolifera by conserving nitrogen in NH4+ form, like the case in microalga bloom. These data, collectively, suggested that Pseudomonas sp. strain SI-3 was a suitable candidate to study the algae-bacteria interaction with U. prolifera and the ecological impacts on algal blooming.